Comparing photocatalytic activity consisting of Sb2S3 and Ag2S on the TiO2–SiO2/TiO2 nanotube arrays-support for improved visible-light-induced photocatalytic degradation of a binary mixture of basic blue 41 and basic red 46 dyes. (3rd August 2021) - Karimi-Shamsabadi, Maryam; Behpour, Mohsen
Abstract: In the present study, a TiO2 nanotube (TNAs) supported Sb2 S3 –TiO2 –SiO2 (STS/TNAs), and Ag2 S–TiO2 –SiO2 (ATS/TNAs) hybrid novel photocatalysts were prepared and characterized by XRD, FT-IR, SEM-EDX, X-ray mapping and, DRS. EIS was employed, and an equivalent circuit model is proposed. Flat-band potential and free carrier concentration were determined by Mott–Schottky plots. The obtained catalysts were used in the photodegradation of a binary mixture of Basic Blue 41 (BB41) and Basic Red 46 (BR46) dyes. Compared with ATS/TNAs, STS/TNAs photocatalyst showed the highest apparent rate constant for BB41 dye, about two times higher, and BR41 dye more than 1.5 times. EIS results agreed with the photodegradation results, so the STS/TNAs system with higher charge transfer ability than the ATS/TNAs system showed the best photodegradation activity. The optimization effect of the amount of Sb2 S3, TiO2, and SiO2 doped on the TNAs on the photocatalytic activity of the STS/TNAs was done using a central composite rotatable design (CCRD) based response surface methodology (RSM). Results have shown catalyst containing 12.2% Sb2 S3 and 27.1% SiO2 /TNAs (S3 TS3 /TNAs) the best photodegradation activity was obtained. The GC-Mass analysis was done to detect the degradation intermediates formed during the photodegradation process. Highlights: STS/TNAs and ATS/TNAs activity was the highest rate constant for BB41 and BR41 dyes than TS/TNAs. The best photodegradation activity was obtained for catalyst containing 12.2% Sb2 S3 and 27.1% SiO2 /TNAs (S3 TS3 /TNAs). Well discussion on interaction effects between the influencing variables in RSM.